Zoneamento geoambiental voltado ao desenvolvimento territorial sustentável do município de Brotas, SP - Guerrero, João Vitor Roque (2020)
The conversion of natural systems into agropastoral systems that occurred in Brazilian landscapes in the last 50 years has produced large-scale impacts on ecosystems, decreasing the quality and quantity of ecosystem services provided. Brazilian environmental policy provides for several instruments and rules that aim to mitigate these impacts, however the lack of inspection and the country's continental size hinder its effectiveness throughout the territory. In this perspective, this study aimed to produce a geoenvironmental zoning for the municipality of Brotas, SP, including essential ecosystem services as a grouping criterion and aiming to contribute to sustainable development on a local scale. The methodological structure had three main stages: i. conduct a geo-environmental diagnosis, using social, economic and environmental aspects, to determine the ecosystem services essential to the current development pattern of the municipality; ii. individually analyze the potential and vulnerabilities of each ecosystem service based on models in geoenvironmental cartography; taking into account the physiographic characteristics and the current pattern of human occupation iii. generate geoenvironmental zoning based on an integrated analysis between ecosystem services and promote territorial planning measures that contribute to efficient territorial planning. The results showed that for the municipality of Brotas both the services provided by groundwater and those provided by soils are highly vulnerable, a fact that occurs due to the conflicting relationship between the naturally sensitive geoenvironmental framework and the inappropriate use of the territory. On the other hand, the mapping indicated high potential for the occurrence of ecosystem services related to ecotourism, a factor that can strengthen the resilience of natural landscapes in the face of the human intervention process. Finally, the zoning letter proposed six different homogeneous zones: consolidation, expansion, recovery, restriction, legal restrictions and consolidated urban areas. These zones indicated the current situation of the productive capacity of ecosystem services and subsidized territorial planning guidelines aimed at balancing the conservation of natural resources and strategies for economic development. Thus, it is expected to contribute to the planning process in the municipality of Brotas in addition to encouraging the insertion of the ecosystem perspective in other Brazilian municipalities.